UKURAN PERUSAHAAN, PERFORMA EKONOMI, PRAKTIK GREEN ACCOUNTING, DAN PENGUNGKAPAN CSR : IMPLIKASINYA TERHADAP NILAI PERUSAHAAN SELAMA PANDEMI COVID-19 DI INDONESIA - Hafidh Purwo Adiyatma (2023)
This research aim to analys an empirical evidence of the effect of Firm Size, Economic Performance, Green Accounting Practice, and CSR Disclousure on Firm Value. This research focuses on raw material and energy companies sector during Pandemic Covid-19 in 2020 until 2021. This research have 74 samples with selected by the purposive sampling method. This research belongs to the quantitative-secondary type. This research use Common Effect Model (CEM) panel data regression. This research use 0.05 significant level The result of the study found that Firm Size has no significant effect to Firm Value, Economic Performance has positive significant effect to Firm Value, Green Accounting Practice has negative significant effect to Firm Value, and CSR Disclousure has no significant effect to Firm Value.